Intentional Artificiality: a principle to reposition the body - Della Costa, Rossana (Revista Brasileira de Estudos da Presença, 2022)
The article develops a reflection on Edward Gordon Craig’s principle of intentional artificiality in order to move the body in the teacher training. The Foucauldian notions of docile body, utopian body and heterotopia are put in operation in laterality with Craigian proposals of the Über-marionnette and the Scene Project, in order to think the puppet's artificial body in relation to the organic body of the Pedagogy undergraduates. It is concluded that there are two coexisting and conflicting ways that operate in the subjectivation processes, one related to the disciplinary order and another that sets the body on for creation.